Elaboration of the method of using etymological analysis at the lessons of ukrainian language in primary school - Лук'яник, Людмила Василівна (ScienceRise: Pedagogical Education, 2016)
The effectiveness of experimental methodology of using etymological analysis at the lessons of Ukrainian language in primary school is proved in the article. The problem of the study is urgent and is in pedagogical and methodological grounding of etymological work with a word, the study of origin and development of the words; explanation of origin of the word by its comparison with related words of the same or other languages, consideration of initial form and meaning of the word. The methodical recommendations as to the mastering of stable skills of etymological explanation of the words by the pupils are grounded in experimental study; the criteria of primary school pupils’ erudition in etymology were elaborated. In the study are considered the problems of etymological analysis at the lessons of Ukrainian language in primary school with combination of grammar and orthographic tasks, using of etymology elements as a mean of activation of schoolchildren’s lexicon with the help of lexical-grammar, stylistic and logical exercises and different techniques of explanation of the meanings of new words